Randomised controlled trial and economic evaluation of a task-based weight management group programme - Hayden McRobbie; Peter Hajek; Sarrah Peerbux; Brennan C. Kahan; Sandra Eldridge; Dominic Trépel; Steve Parrott; Chris Griffiths; Sarah Snuggs; Katie Myers Smith (BMC, 2019)
Abstract Background Obesity is a rising global threat to health and a major contributor to health inequalities. Weight management programmes that are effective, economical and reach underprivileged groups are needed. We examined whether a multi-modal group intervention structured to cater for clients from disadvantaged communities (Weight Action Programme; WAP) has better one-year outcomes than a primary care standard weight management intervention delivered by practice nurses (PNI). Methods In this randomised controlled trial, 330 obese adults were recruited from general practices in London and allocated (2:1) to WAP (N = 221) delivered over eight weekly group sessions or PNI (N = 109) who received four sessions over eight weeks. Both interventions covered diet, physical activity and self-monitoring. The primary outcome was the change in weight from baseline at 12 months. To indicate value to the NHS, a cost effectiveness analysis estimated group differences in cost and Quality-Adjusted Life-Years (QALYs) related to WAP. Results Participants were recruited from September 2012 to January 2014 with follow-up completed in February 2015. Most participants were not in paid employment and 60% were from ethnic minorities. 88% of participants in each study arm provided at least one recorded outcome and were included in the primary analysis. Compared with the PNI, WAP was associated with greater weight loss overall (− 4·2 kg vs. − 2·3 kg; difference = − 1·9 kg, 95% CI: -3·7 to − 0·1; P = 0·04) and was more likely to generate a weight loss of at least 5% at 12 months (41% vs. 27%, OR = 14·61 95% CI: 2·32 to 91·96, P = 0·004). With an incremental cost-effectiveness ratio (ICER) of £7742/QALY, WAP would be considered highly cost effective compared to PNI. Conclusions The task-based programme evaluated in this study can provide a template for an effective and economical approach to weight management that can reach clients from disadvantaged communities. Trial registration ISRCTN ISRCTN45820471. Registered 12/10/2012 (retrospectively registered).